2014
DOI: 10.3945/ajcn.114.083402
|View full text |Cite
|
Sign up to set email alerts
|

The causal role of breakfast in energy balance and health: a randomized controlled trial in lean adults

Abstract: Background: Popular beliefs that breakfast is the most important meal of the day are grounded in cross-sectional observations that link breakfast to health, the causal nature of which remains to be explored under real-life conditions.Objective: The aim was to conduct a randomized controlled trial examining causal links between breakfast habits and all components of energy balance in free-living humans.Design: The Bath Breakfast Project is a randomized controlled trial with repeated-measures at baseline and fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
264
5
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 186 publications
(293 citation statements)
references
References 42 publications
22
264
5
2
Order By: Relevance
“…A number of intervention studies have investigated breakfast omission over longer periods of time, often using food records to estimate daily energy intake ( Table 2). Whilst the results of these studies are slightly more varied, once again the weight of evidence suggests that omission of breakfast in the morning will reduce daily energy intake in the longer term (14,37,41) . In one of these studies, a reduction in energy intake was observed in a 6 week between groups breakfast intervention study.…”
Section: Multiple Exposure Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of intervention studies have investigated breakfast omission over longer periods of time, often using food records to estimate daily energy intake ( Table 2). Whilst the results of these studies are slightly more varied, once again the weight of evidence suggests that omission of breakfast in the morning will reduce daily energy intake in the longer term (14,37,41) . In one of these studies, a reduction in energy intake was observed in a 6 week between groups breakfast intervention study.…”
Section: Multiple Exposure Studiesmentioning
confidence: 99%
“…after 12·00 hours were unaffected by consumption or omission of breakfast in the morning, resulting in a reduced energy intake of approximately 2300 kJ/d when breakfast was omitted (37) . In contrast to this, Halsey et al (42) found no difference in daily energy intake, independent of consumption or omission of an ad libitum breakfast.…”
Section: Multiple Exposure Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst observational studies are useful for establishing a potential link between a behavior and an outcome, randomized controlled trials are essential in order to make definitive causal statements. More recent studies using free-living designs over periods of weeks and months [5][6][7][8], combined with evidence from more tightly-controlled laboratory studies conducted within a single day [9][10][11] are beginning to address the causality of breakfast consumption, body weight regulation and health, whilst providing mechanistic insight into any causal effects.…”
mentioning
confidence: 99%